(untitled) (Journal of the College of Basic Education, 2022)
The research aimed to identify the point of control of the teachers of some faculties of Al-Mustansiriya University from their point of view and whether it was. Are there statistically significant differences in the point of control according to the variable of gender, specialization and length of service. The research was limited to a sample of teachers from some colleges of Al-Mustansiriya University, their number was (160) teachers, and they were selected from (6) colleges. And after using the statistical means represented by the Pearson correlation coefficient and the t-test for one sample and the t-test for two independent samples. The researcher reached the following results:- The locus of control for the teaching of some university faculties was inclined towards the internal one. There is no statistically significant difference in the point of control between male and female teachers. There are no differences in the direction of control between teachers with a taste for scientific specialization and teachers with a humanitarian specialization. 4.There is no statistically significant difference in the destination of control according to the variable of service period.